2014
DOI: 10.3109/10826084.2014.891616
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption, Dependence, and Treatment Barriers: Perceptions Among Nontreatment Seekers with Alcohol Dependence

Abstract: Suffering from alcohol dependence, as well as realizing the need for, and entering treatment, were associated with shame and stigma, and were strong barriers to treatment. Other barriers included the desire to deal with alcohol problems on one's own and the view that seeking treatment required total abstinence. Negative health-effects were mainly a nonissue. The participants' knowledge about treatment options was limited to lifelong abstinence, medication with Disulfiram and residential treatment. These were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
105
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(119 citation statements)
references
References 29 publications
(38 reference statements)
6
105
0
1
Order By: Relevance
“…This increase could be linked to higher rates of major depression for this subsample in 2001–02 versus 1991–92 (20 and 12%, respectively); Schomerus et al (2011) reported a positive relationship between depressive symptoms and self-stigma in alcoholics. Stigmatization has consistently been linked to treatment usage (Keyes et al, 2010; Wallhed-Finn et al, 2014). Keyes et al (2010) examined perceived stigmatization of alcoholism in adults with AUD from the 2004–05 NESARC.…”
Section: Discussionmentioning
confidence: 99%
“…This increase could be linked to higher rates of major depression for this subsample in 2001–02 versus 1991–92 (20 and 12%, respectively); Schomerus et al (2011) reported a positive relationship between depressive symptoms and self-stigma in alcoholics. Stigmatization has consistently been linked to treatment usage (Keyes et al, 2010; Wallhed-Finn et al, 2014). Keyes et al (2010) examined perceived stigmatization of alcoholism in adults with AUD from the 2004–05 NESARC.…”
Section: Discussionmentioning
confidence: 99%
“…The widespread perception in our study of alcoholism as an illness is not reflected in greater access to treatment. An alternative explanation is that while the majority of patients see that treatment for alcoholism is only focused on abstinence, this is not an objective that 45.7% initially set for themselves (Adamson, Heather, Morton, & Raistrick, 2010;Heather, Adamson, Raistrick, & Slegg, 2010); some studies suggest that this is one of the principal barriers to treatment (Wallhed Finn, Bakshi, & Andreasson, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Sudden alcohol withdrawal is dangerous for dependent drinkers, in the most serious cases causing seizures. At the last estimate for Scotland, only one in four alcohol dependent drinkers was accessing alcohol services (Beeston et al, 2014), andWallhed-Finn, Bakshi, andAndreasson (2014) reported that a minority of those with alcohol dependence seek and undergo treatment. All participants in our study have received treatment relating to their drinking at least once (their recruitment site), but there are likely many more (whose numbers we do not know) who have not engaged with services, or received support.…”
Section: Discussionmentioning
confidence: 99%